Warga Samin di Kudus dan Pelestarian Tradisi Budaya Jawa - Moh Rosyid (Universitas Padjadjaran, 2020)
This study aims at describing some of the Javanese cultural tradition that are preserved and neglected by the Samin (puritan Javanese community) in Kudus; and their reasons for doing so. Data of this study were collected through in-depth interview to Samin local leader and observation to the daily activities of the Samin. Data were analysed according to the principal of descriptive qualitative. The results of this study suggest that the Samin preserves some of Javanese traditions, such as own a sacred dagger (keris), gems, wearing black clothes, folk songs, gamelan and poetry. Keris usually owned by male leadersand they use it in healing, protecting the land, and serves as spiritual partner to the owner. Meanwhile, the Samin no longer preserve some other Javanese traditions; such as dance and arts; and raising buffalo and turtledove as livelihood due to limited resources. The Samin preserves their ancestral way of life and inherit it to their younger generation through oral tradition.